The effects of glycerol addition to the mechanical properties of thermoplastic films based on jackfruit seed starch [Kesan penambahan gliserol pada sifat mekanik filem thermoplastik berdasarkan kanji biji nangka] - Ahmad Shahrim, Nur’Aishah Ahmad; Sarifuddin, Norshahida; Mohd Zaki, Hafizah Hanim; Ahmad Azhar, Ahmad Zahirani (Faculty of Science and Technology, Universiti Kebangsaan Malaysia, 2018)
Thermoplastic films based on 3 wt.% jackfruit seed starch were prepared using 5 to 30 wt.% glycerol as plasticizer via solution casting method. The aim of this study is to investigate the effect of glycerol on the mechanical properties of films. According to the analysis, the optimum tensile strength of the film was obtained at 4.40 MPa, which revealed that the native starch granules were converted into a continuous phase in the presence of glycerol as indicated by scanning electron microscopy. The incorporation of glycerol in starch also showed the formation of hydrogen bond evidenced by Fourier transform infrared spectroscopy.